A case of generalized lichen planus pigmentosus: an atypical clinical variety - Li, Rong; Zhang, Jia-an; Jiang, Yi-Qun; Chen, Kun (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
A 38-year-old woman was referred to our dermatology department with a 3-month history of disseminated grey-brown macules located on limbs, which extended rapidly to the trunk. She had an occupational history as an orchard farmer and no history of medication. Initially one or two light brown macules appeared on her forearms (Figure 1 A) with mild pruritus and gradually spread and developed into grey-brown patches on the chest and abdomen (Figure 1 B). The oral mucosa and nails were not involved. A biopsy specimen was taken from a macule on her abdomen. Histopathology revealed epidermis atrophy, basal layer vacuolization, lymphocytic band-like infiltrate and marked pigmentation incontinence in superficial dermis (Figures 1 C, D). The routine laboratory data were within normal limits or negative. Based on clinical and histopathologic findings, these clues favour the diagnosis of generalized lichen planus pigmentosus (LPP). Drugs including potent topical corticosteroids, oral steroids, topical calcineurin inhibitors and skin-lightening agents were recommended for LPP. The patient got a relief after 2 months by using topical corticosteroids.